2017
DOI: 10.14302/issn.2691-5014.jphn-17-1424
|View full text |Cite
|
Sign up to set email alerts
|

Implementing High Energy Liquid Nutrition, Omega-3 Fatty Acids and Nutritional Supplements for the Treatment of Anorexia Nervosa

Abstract: Objective: To assess the effect of different treatment approaches on the course of anorexia nervosa (AN) over time. Methods: The subjects were 27 hospitalized AN patients. In our retrospective analysis we compared weight gain in two groups. While one group was treated with a standard oral refeeding protocol (historical control) through January 2013 (N=16), the second group (highly standardized refeeding protocol) received a high energy liquid nutrition and nutritional supplements including omega-3 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Moreover, we observed a significant increase of heart rates and decrease of HRV during refeeding which could explain the discomfort due to this "autonomic switch" and the massive resistance against this therapy from the patients [6]. Based on this pathophysiological understanding, we changed our therapeutic concepts and can significantly improve weight gain during in-hospital refeeding [7]. Within the last 13 years and more than 100 Holter ECG's in patients with AN that include longtime follow up data, we increasingly began to doubt our primary assumption that the HRV changes are caused solely by the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, we observed a significant increase of heart rates and decrease of HRV during refeeding which could explain the discomfort due to this "autonomic switch" and the massive resistance against this therapy from the patients [6]. Based on this pathophysiological understanding, we changed our therapeutic concepts and can significantly improve weight gain during in-hospital refeeding [7]. Within the last 13 years and more than 100 Holter ECG's in patients with AN that include longtime follow up data, we increasingly began to doubt our primary assumption that the HRV changes are caused solely by the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 84%
“…Within the last 10 years, we have found that children with anorexia nervosa have learned to modulate their hyperactive stress response by starvation. During in-hospital refeeding, we reactivate the hyperactive stress response, which is indicated by highly significant increases in mean heart rates and postural orthostatic tachycardia syndrome [13]. In patients with anorexia nervosa, the increase in resting energy expenditure during…”
Section: Diagnosticsmentioning
confidence: 96%